Study on Multi-body Dynamics of Cycloidal Pin Wheel Transmission of RV Reducer - Zheng Peng; Liu Xiaochao; Zhao Wenhui; Liang Quan; Guo Guangyu; Sun Rui (Jixie chuandong)
The meshing transmission part of the cycloidal pin wheel is the key structure of the RV reducer，the simulation analysis of virtual prototype based on multi-body dynamics is a common method to study the dynamic characteristics of the RV reducer. Taking into account different loads and different working conditions，the RV reducer is simulated and analyzed based on multi-rigid dynamics. The simulation results visually show the changes of the meshing characteristics of the cycloidal pin teeth under different working conditions. The rigid-flexible coupling technique is used to extract the continuous node stress curve for analysis，and the position and size of the maximum contact force during meshing are determined，and a theoretical basis for the research and improvement on the way of subsequent shaping is provided.